Electron tunneling into surface states through an inhomogeneous barrier: asymptotically exact solution of the problem and STM theory - Khotkevych, N.V.; Kolesnichenko, Yu.A.; Ruitenbeek, J.M. van (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We have found an asymptotically exact solution of the Schrödinger equation for electrons tunneling into surfacestates through an inhomogeneous barrier of large amplitude. Assuming an elliptic dispersion law for the charge carriers the “standing wave” pattern in the conductance of the system resulting from the electron scattering by a single defect in the vicinity of the surface is analyzed.